PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI MENGAJAR TERHADAP KINERJA GURU DI SMP NEGERI SE-KECAMATAN BUAY PEMUKA PELIUNG KAB. OKU TIMUR - Sari, Rita; Arafat, Yasir; Mulyadi, Mulyadi (Jurnal Manajemen Pendidikan, 2026)
The purpose of this study was to examine the influence of pedagogical competence and teaching motivation on teacher performance at public junior high schools (SMP Negeri) in the Buay Pemuka Peliung Subdistrict, East OKU Regency. Specifically, this study aimed to investigate the effect of pedagogical competence on teacher performance, the effect of teaching motivation on teacher performance, and the simultaneous effect of pedagogical competence and teaching motivation on teacher performance. This research was conducted at SMP Negeri in the Buay Pemuka Peliung Subdistrict, East OKU Regency using a descriptive quantitative research method. The sample consisted of fifty respondents, and data were collected using questionnaires. The results indicated that pedagogical competence and teaching motivation each partially affect teacher performance. Simultaneously, both pedagogical competence and teaching motivation influence teacher performance. The contribution of the independent variables, namely pedagogical competence, teaching motivation, and training, to teacher performance was very high, while the remaining influence came from other factors such as skills and expertise, knowledge, work planning, personality, organizational culture, and job satisfaction.